2003
DOI: 10.1063/1.1621457
|View full text |Cite
|
Sign up to set email alerts
|

Tunable, narrow-band light emission from size-selected Si nanoparticles produced by pulsed-laser ablation

Abstract: We have demonstrated narrow-band visible light emission from size selected silicon nanoparticles (np-Si), with a wavelength controlled by size tuning. The np-Si were synthesized by pulsed-laser ablation of a silicon single-crystal target in high-purity He background gas. A postannealing process improved morphology and crystallinity. Using a differential mobility analyzer, nanoparticles were classified with a diameter tunable from 3 to 6 nm. Monodispersed np-Si deposited on substrate exhibited a sharp photolumi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
42
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 68 publications
(44 citation statements)
references
References 26 publications
2
42
0
Order By: Relevance
“…The most critical characteristic of nanoparticles is that the properties (electrical, optical, magnetic, and so on) depend strongly on the size and size distribution of the particles (Kim et al, 2014). For example, silicon nanoparticles are photoluminescent in the visible spectrum at room temperature (Kenemitsu, 1995;Yoshida et al, 1998); the wavelength of the emitted light can be controlled with the particle size (Orii et al, 2003a). Nano-sized titania particles have also gathered attention as building blocks for photovoltaic devices (O'regan and Gratzel, 1991) and for photocatalytic applications (Fujishima and Honda, 1972).…”
Section: Introductionmentioning
confidence: 99%
“…The most critical characteristic of nanoparticles is that the properties (electrical, optical, magnetic, and so on) depend strongly on the size and size distribution of the particles (Kim et al, 2014). For example, silicon nanoparticles are photoluminescent in the visible spectrum at room temperature (Kenemitsu, 1995;Yoshida et al, 1998); the wavelength of the emitted light can be controlled with the particle size (Orii et al, 2003a). Nano-sized titania particles have also gathered attention as building blocks for photovoltaic devices (O'regan and Gratzel, 1991) and for photocatalytic applications (Fujishima and Honda, 1972).…”
Section: Introductionmentioning
confidence: 99%
“…These ns-Si materials and devices can be produced by electrochemical anodization (i.e., porous Si [12]), chemical vapor deposition (CVD) using thermal decomposition of SiH 4 [13-15], Si ion implantation into a SiO 2 matrix [16], and deposition of amorphous Si/SiO 2 layers followed by thermal crystallization [17][18][19]. These ns-Si materials and devices produce an efficient and tunable light emission in the near-infrared and visible spectral region [20,21]. Also, it has been shown that under photoexcitation with energy density >10 mJ/cm 2 , optical gain is possibly Silicon Nanocrystals: Fundamentals, Synthesis and Applications.…”
mentioning
confidence: 99%
“…20 Stokes/anti-Stokes Raman spectra in a Si/SiGe multilayer sample on a Si substrate collected using different excitation wavelengths (indicated). Spectra are shifted vertically for clarity and c-Si Raman spectrum is shown for comparison.…”
mentioning
confidence: 99%
“…The chain agglomerates of metal oxides generated by laser ablation show elastic properties under the electron microscope (Ogawa et al, 2000). Laser-synthesized silicon nanoparticles emit visible light at room temperature (Yamada et al, 1996;Orii et al, 2003). El-Shall (1996) developed a method of laser-vaporization-controlled condensation (LVCC) and used it to fabricate various kinds of nanoparticles.…”
Section: Introductionmentioning
confidence: 99%
“…This combination of laser ablation and LP-DMA provides a powerful tool for the analysis of various properties of nanoparticles. In the last 2 years, for example, we have used this combination to study the size-dependent optical properties of Si nanoparticles (Orii et al, 2003) and the magnetic properties of Ni nanoparticles .…”
Section: Introductionmentioning
confidence: 99%